Consequences of nitrogen mineralization dynamics for soil health restoration of degraded tea-growing soil using organic amendments - Liyanage, Mahesh; M. Hanafi, Mohamed; Sulaiman, Muhammad Firdaus; Ismail, Roslan; Gunaratne, Gamini Perera; Dharmakeerthi, Randombage Saman; Rupasinghe, Geethika; Mayakaduwa, Amoda Priyangi (Instituto de Investigaciones Agropecuarias, 2021)
Understanding of N mineralization dynamics of frequently available organic amendments in the tea (Camellia sinensis (L.) O. Kuntze) ecosystem has greater importance in land restoration. Hence, this study focused on assessing the effects of organic amendments on N mineralization and soil quality improvement in tea growing soil. Garden compost (CMP), Gliricidia (Gliricidia sepium (Jacq.)) leaves (GLI), charged tea waste biochar (CBC), tea waste (TW), and tea waste biochar without charging (RBC) were incubated with soil at a rate of 186 mg N kg-1. Incubated soils were analyzed periodically for soil pH, available NO3 --N, NH4 +-N, soil P, and S for 120-d. Microbial biomass C (MBC), protease, urease, phosphatase, and dehydrogenase activities were determined at the end of the incubation. All amendments showed different N mineralization patterns. Gliricidia, CMP, and TW released N by 94%, 43%, and 24%, respectively. Gliricidia showed the highest peak of NH4 +-N after 21-d incubation, depicting rapid ammonification. Charged BC and RBC showed N immobilization throughout the incubation period, which finally amounted to 12% and 17%, respectively. Gliricidia showed 0.79 mg d-1 maximum N mineralization rate and 150 mg kg-1 total mineralizable N. The N mineralization was sequenced as GLI > CMP > TW > CBC > RBC. All amendments showed more than 45% increase in MBC, where Gliricidia gave the highest (146%) compared to the control. Application of CBC promotes all enzyme activities by > 90% over control. In conclusion, GLI meets the immediate plant N requirement, and CBC significantly improves the degraded soil quality.